1978
DOI: 10.1007/bf01463553
|View full text |Cite
|
Sign up to set email alerts
|

Children of depressed and schizophrenic mothers

Abstract: A sample of psychotic mothers and their children who were five years or younger when first recruited for our study of high risk children was followed up five years later. The current sample, obtained from our previous work, consisted of 18 schizophrenic, 12 depressed and psychotic, and 22 well mothers and their six to 12 year old children. The mothers were equated for education and age, and the children for sex and age. Cognitive style tests and interviews measuring social adjustment and functioning were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…In the two studies in which differences were not found-the Boston (Cohler, Grunebaum, Weiss, Garner, & Gallant, 1977;Herman, Mirsky, Ricks, & Gallant, 1977) and the Danish Birth Cohort (Orvaschel et al, 1979) studies--the relative simplicity of the tasks may account for the negative findings (ErlenmeyerKimling et al, 1982;Nuechterlein, 1983). Versions of the Continuous Performance Test (CPT), a test of sustained visual attention, that produce very few errors in performance do not differentiate well between children of schizophrenics and children of normal parents Cohler et al, 1977;Erlenmeyer-Kimling et al, 1982;Erlenmeyer-Kimling, Kestenbaum, et aI., 1984;Grunebaum, Cohler, Kauffman, & Gallant, 1978;Nuechterlein, 1983), whereas more complex versions appear to work very well in this regard Erlenmeyer-Kimling, Cornblatt,& Golden, 1983;Nuechterlein, 1983;Rutschmann, Cornblatt, & Erlenmeyer-Kimling, 1977). Task parameters, rather than the type of process or sensory modality that the tests tap, appear to determine whether a particular test will successfully distinguish high-risk subjects.…”
Section: Attention and Information Processingmentioning
confidence: 93%
“…In the two studies in which differences were not found-the Boston (Cohler, Grunebaum, Weiss, Garner, & Gallant, 1977;Herman, Mirsky, Ricks, & Gallant, 1977) and the Danish Birth Cohort (Orvaschel et al, 1979) studies--the relative simplicity of the tasks may account for the negative findings (ErlenmeyerKimling et al, 1982;Nuechterlein, 1983). Versions of the Continuous Performance Test (CPT), a test of sustained visual attention, that produce very few errors in performance do not differentiate well between children of schizophrenics and children of normal parents Cohler et al, 1977;Erlenmeyer-Kimling et al, 1982;Erlenmeyer-Kimling, Kestenbaum, et aI., 1984;Grunebaum, Cohler, Kauffman, & Gallant, 1978;Nuechterlein, 1983), whereas more complex versions appear to work very well in this regard Erlenmeyer-Kimling, Cornblatt,& Golden, 1983;Nuechterlein, 1983;Rutschmann, Cornblatt, & Erlenmeyer-Kimling, 1977). Task parameters, rather than the type of process or sensory modality that the tests tap, appear to determine whether a particular test will successfully distinguish high-risk subjects.…”
Section: Attention and Information Processingmentioning
confidence: 93%
“…reported deviant cognitive or linguistic development among infants or preschoolers of low-income mothers with depressive symptoms (Coghill, Caplan, Alexandra, Robson, & Kumar, 1986;Goodman, 1987;Grunebaum, Cohler, Kaufman, & Gallant, 1978;Hubbs-Tait, Fusco, Hann, Osofsky, & Hughes, 1992;Lyons-Ruth, Zoll, Connell, & Grunebaum, 1986) as well as among low-income preschoolers with behavior problems (Erickson, Sroufe, & Egeland, 1985).…”
mentioning
confidence: 96%
“…Some family relatives of affected patients also carry the endophenotype, although not the disorder phenotype (i.e., affective symptoms) in the case of BD (Adida et al, 2012). In fact, some studies also described attention deficits in unaffected relatives of individuals with mood disorders (Bora, Yucel, & Pantelis, 2009;Brotman, Rooney, Skup, Pine, & Leibenluft, 2009;Grunebaum, Cohler, Kauffman, & Gallant, 1978;Klimes-Dougan, Ronsaville, Wiggs, & Martinez, 2006;Zalla et al, 2004). Gottesman, & Gould (2003) discussed endophenotypes and suggested five criteria that should be characteristic of a trait to qualify it as an endophenotype.…”
Section: Discussionmentioning
confidence: 99%